A review of the current laboratory practice in Malaysian university: a preliminary study - Radin Salim, Kamilah; Puteh, Marlia; Mohd. Daud, Salwani (2009)
The rapid increase in technological developments worldwide has provided the impetus for change in engineering training and education. To meet these transformations, it is crucial that engineering education programs generate graduates with technical and professional skills to become easily accustomed to working environment. Educational institutions contribute to this agenda by outlining the attributes that are central in producing graduates with satisfactory levels of knowledge, skills and attitudes. This paper investigates how these knowledge and skills could be acquired through laboratory works and laboratory reports. Laboratory experiments are practical activities used to integrate theory with practice, and are significant in enabling the students to make the connections between theory and practice. Which types of laboratory skills are commonly practised during laboratory sessions in an engineering course? Is the current laboratory assessment valid? This paper will examine these issues further and recommend several measures to enhance the practice of laboratory experiments in Malaysian universities.